ICP-OES analysis of heavy metals in cosmetic products on the Macedonian market - Marina Denkovska; Viktorija Duridanska; Tatjana Kadifkova Panovska (Makedonsko Farmacevtski Bilten)
The aim of this research was to determine concentration of lead (Pb), cadmium (Cd), chromium (Cr), and nickel (Ni) in selected cosmetic products available on the Macedonian market. The sample preparation procedure consisted of acid digestion followed by evaporation to dryness and dissolving the dry residue with 2% HNO3 for further analysis. Heavy metal content was determined utilizing Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). Lead was found in 18 of the analyzed samples and its concentration ranged 0.07 to 1.23 mg/kg. Cadmium wa found in 14 samples and its concentration ranged 0.05 to 0.10 mg/kg. Chromium was found in 13 of the samples and its concentration ranged 0.07 to 3.25 mg/kg. Nickel was found in 8 of the samples and its concentration ranged 0.07 to 2.58 mg/kg. The obtained results from the study show that heavy metal levels in the selected cosmetic products were within the permissible levels according to the Macedonian legislation. However, given the toxic effects these substances exert on a long term basis, their content in cosmetic products, should be continuously monitored in order to assure lowest risks as well as safe application of these products.